Reaping the Benefits of Migration in an Ageing Europe - Jesús Crespo Cuaresma; Peter Huber; Anna Raggl (WWWforEurope, 2015)
Unless labour force participation in Europe increases enormously in the coming decades, the current demographic dynamics will pose gigantic challenges to the sustainability of public finance. Migration (and thus migration policy) can thus be seen as a central topic which will remain on top of the policy agenda. The aim of this policy brief is to summarize the knowledge gained by the research efforts on this issue in the framework of WWWforEurope and to provide policymakers with new methods and research results which will allow them to better quantify the effects of policy changes.
Keywords: 330; Bevölkerungsentwicklung; Alternde Bevölkerung; Einwanderung; Migranten; Arbeitsmarktintegration; Migrationspolitik; EU-Staaten